Assessment of efficiency of use of sources of financing of investments (Путеводитель предпринимателя, 2020)
In the article the evaluation of sources of funding, investment projects, and the current activities of the organizations. The technique, which allows to estimate the influence of the structure and magnitude of funding on the financial performance of organizations.